Formalizing Latin American Perspectivism: A Neutrosophic MultiPerspectivism Model - Maikel Y. Leyva Vázquez; Florentin Smarandache (Neutrosophic Sets and Systems)
This paper addresses the challenge of formally modeling the complex, often contradictory, knowledge systems inherent in Latin American decolonial thought. It introduces Neutrosophic MultiPerspectivism, a framework that operationalizes philosophical perspectivism using neutrosophic logic. We posit that knowledge is situated and truth is mediated by the observer's viewpoint—a concept with roots in Nietzschean philosophy but which finds distinct expression in Amerindian cosmologies and pluralistic legal systems. The primary method involves proposing a "Neutrosophic MultiPerspectivism Model," which uses MultiNeutrosophic sets to represent subjective perspectives as a triplet of truth, indeterminacy, and falsity sequences ⟨T, I, F⟩. A key result is the development of a similarity function that quantifies the affinity between different perspectives, transforming qualitative viewpoints into analyzable data. This model is applied to a case study of a legal land dispute, where it successfully reveals hidden structural similarities—such as a shared absolutist reasoning style between opposing parties—and identifies potential strategic alliances. The main conclusion is that neutrosophic logic provides a robust mathematical tool to navigate the ambiguity and plurality of perspectivist realities, moving beyond mere acknowledgment of difference to its formal analysis and potential integration.